Necitumumab for the treatment of squamous cell non-small cell lung cancer. (January 2018) - Brinkmeyer, Jessica K; Moore, Donald C
Non-small cell lung cancer is the most common form of lung cancer, accounting for about 85% of all cases and is further subdivided into adenocarcinoma, squamous cell, and large cell carcinoma. Necitumumab (Portrazza™, Eli Lilly and Company) is an anti-epidermal growth factor receptor monoclonal antibody approved for the first-line treatment of squamous cell non-small cell lung cancer in combination with cisplatin and gemcitabine. The safety and efficacy of necitumumab has been evaluated in two-phase III clinical trials, one demonstrating a lack of efficacy in non-squamous non-small cell lung cancer and another demonstrating improvement in overall survival and progression-free survival in squamous cell non-small cell lung cancer. Necitumumab is associated with adverse events such as infusion reactions, hypomagnesemia, diarrhea, and dermatological toxicities. Although considered a safe and effective treatment option for squamous cell non-small cell lung cancer, the clinical utility of necitumumab may be limited due to the high cost of the drug as well as added toxicity when combined with cisplatin and gemcitabine. Several clinical trials are ongoing in order to further investigate the utilization of necitumumab.